Isolation and Identification of Lactic Acid Bacteria from Natural Whey Cultures of Buffalo and Cow Milk - Rosangela Marasco; Mariagiovanna Gazzillo; Nicoletta Campolattano; Margherita Sacco; Lidia Muscariello (Foods, 2022)
In southern Italy, some artisanal farms produce mozzarella and caciocavallo cheeses by using natural whey starter (NWS), whose microbial diversity is responsible for the characteristic flavor and texture of the final product. We studied the microbial community of NWS cultures of cow’s milk (NWSc) for the production of caciocavallo and buffalo’s milk (NWSb) for the production of mozzarella, both from artisanal farms. Bacterial identification at species and strain level was based on an integrative strategy, combining culture-dependent (sequencing of the 16S rDNA, species/subspecies-specific Polymerase Chain Reaction (PCR) and clustering by Random Amplified Polymorphic DNA-Polymerase Chain Reaction (RAPD-PCR) and culture-independent (next-generation sequencing analysis, NGS) approaches. Results obtained with both approaches showed the occurrence of five species of lactic acid bacteria in NWSb (Lactococcus lactis subsp. lactis, Lactobacillus fermentum, Streptococcus thermophilus, Lactobacillus delbrueckii, and Lactobacillus helveticus) and five species in NWSc (Lc. lactis subsp. lactis, Enterococcus faecium, and S. thermophilus, Lb. helveticus, and Lb. delbrueckii), with the last two found only by the NGS analysis. Moreover, RAPD profiles, performed on Lc. lactis subsp. lactis different isolates from both NWSs, showed nine strains in NWSb and seven strains in NWSc, showing a microbial diversity also at strain level. Characterization of the microbiota of natural whey starters aims to collect new starter bacteria to use for tracing microbial community during the production of artisanal cheeses, in order to preserve their quality and authenticity, and to select new Lactic Acid Bacteria (LAB) strains for the production of functional foods.